2009
DOI: 10.3793/jaam.6.46
|View full text |Cite
|
Sign up to set email alerts
|

Photoaging of the skin

Abstract: Photoaging of the skin46 Solar radiation at the surface of the earth includes ultraviolet radiation (UV : 290-400nm), visible light (400-760nm) and infrared radiation (760nm-1mm) (Fig 1).Extrinsic skin aging is superimposed on intrinsic skin aging process and is due primarily to UVR (solar ultraviolet radiation) and partly by other factors, such as infrared light, smoking and air pollutants. UVR has been divided into ultraviolet B (UVB: 290-320nm) which principally generates pyrimidine dimer type DNA damage th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 147 publications
1
94
0
9
Order By: Relevance
“…63 Evidences based on research demonstrated that pomegranate shows photo-protection activity [ Table 2]. Previous finding revealed that pomegranate seed oil was shown to stimulate keratinocyte proliferation in monolayer culture.…”
Section: Photo-protection Activitymentioning
confidence: 99%
“…63 Evidences based on research demonstrated that pomegranate shows photo-protection activity [ Table 2]. Previous finding revealed that pomegranate seed oil was shown to stimulate keratinocyte proliferation in monolayer culture.…”
Section: Photo-protection Activitymentioning
confidence: 99%
“…Acute UV exposure stimulates angiogenesis through vascular endothelial growth factor (VEGF) upregulation via the MEK-ERK pathway activation and down regulation of thrombospond in-1 (TSP-1) through activation of the P13K-Akt pathway in the human epidermis. However, in chronic exposure, decreased blood vessels have been found on skin damaged by UV (Ichihashi et al, 2009 UVB radiation induces VEGF-A in the basal layer of the epidermis, whereas the expression of TSP-1 is downregulated in the epidermis. Thus, the down regulation of TSP-1 and the upregulation of VEGF-A appear to contribute to a molecular level trigger of the induction of angiogenesisin the skin due to UVB radiation (Sawane and Kajiya, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…With intrinsic skin aging, there were no significant differences in vascular density, although a decrease in blood vessel size was found between young skin and old skin. In one study on papillary dermis skin photo aging, donors' aged skin showed significant differences in the size of blood vessels and the number of blood vessels when compared to young skin (Ichihashi et al, 2009). Acute UV exposure stimulates angiogenesis through vascular endothelial growth factor (VEGF) upregulation via the MEK-ERK pathway activation and down regulation of thrombospond in-1 (TSP-1) through activation of the P13K-Akt pathway in the human epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological actions of phenolic antioxidants against free radical scavenging is very important to inhibit wrinkle, because skin which repeatedly exposed to ultraviolet light every day, can occurred wrinkles. 19 The presence of some phytoconstituents, such as phenols, flavonoids and tannins in seagrasses may be the cause of antioxidant activity in preventing occurred wrinkles or inhibit collagenase activity. 20 The selection of solvent types is essential for efficiency of the extraction process, because the compound of solvent with different polarity provides different antioxidant potential.…”
Section: Total Phenolic Content (Tpc) Of T Hempricii Extractmentioning
confidence: 99%